A method for analyzing room modal response using auralization. (30th June 2022) - Algargoosh, Alaa; Navvab, Mojtaba; Granzow, John
Highlights: Method for analyzing room modes using auralization. Analyzing room modes of spaces with complex geometry, various materials, and source locations. Auralization allows identifying the frequencies that the room will amplify or dampen. A tool to inform design decisions based on acoustic amplification needs across frequency bands. Abstract: Room modes are the resonances that amplify some frequencies and suppress others, changing the sound's tonal characteristics. As reported in some historic and worship spaces, the resulting resonances can provoke an emotional response that enhances the listener's experience. Traditional methods do not allow for calculating room modes of spaces with complex geometries such as worship spaces. Hence, this paper aims to develop a method to analyze the room modes and amplified frequencies for such spaces and identify the frequency bands amplified based on the room's response to a continuous sound source, considering its frequency characteristics. The method was inspired by Lucier's sound art piece "I am sitting in a room, " in which he recorded his speech, then played the recording and rerecorded it in the same room multiple times until the resonant frequencies of the room became dominant. This research explored the potential of analyzing room modes and amplified frequencies by replicating the same iterative process using auralization (convolution). The results showed that, unlike traditional room mode calculation methods, the proposed method considers both surface materials and the sound source location in calculating room modes. In addition, it considers the frequency characteristics of the sound source in the analysis of the frequencies amplified by the room when playing a particular sound. The last section of the paper demonstrates an application of the method in a worship space with complex geometry.